The Functional and Identity Indispensability Scale (FIIS) - Guerra, R.; Rodrigues, D.; Gaertner, S. L.; Deegan, M.; António, R. (International Journal of Intercultural Relations, 2016)
This research further elaborated the concept of indispensability by developing and testing a new measure, the Functional and Identity Indispensability Scale (FIIS), to assess two dimensions on which groups can claim indispensability: functional indispensability and identity indispensability. In Study 1 we developed and validated the FIIS with a sample of 452 American college students. Results showed the expected two-factor structure and supported the prediction that identity and functional are two distinct, but related, forms of indispensability. FIIS showed a consistent structure across majority and minority members and the reliability of the two subscales was good. In Study 2, a sample of 154 White-American citizens evaluated the perceived indispensability (FIIS) of three minority groups: African-Americans, Hispanic-Americans, and Asian-Americans. Results showed the scale’s sensitivity. Participants attributed greater identity (vs. functional) indispensability to African-Americans, whereas the pattern was reversed for Asian-Americans. No differences were found for Hispanic-Americans. Criterion validity was supported by (a) positive associations with competence and warmth, (b) negative associations with negative emotions and with social distance towards all minority group targets. The psychometric properties of the FIIS suggest its potential to be valuable addition to the existing literature on common identities and intergroup relations.